Application of laser on enamel surface with three types of bioactive glasses-based resin infiltrants: An in vitro study. (May 2023) - Khan, Abdul Samad; AlDahlan, Bashayer Ghazi; Maghrabi, Nusaybah Hamza; Albilali, Hind Waleed; Ahmed, Syed Zubairuddin; Shah, Asma Tufail; Haridy, Rasha; Akhtar, Sultan; Talal, Ahmed
Abstract: Objective: The study aimed to evaluate and compare the surface micro-hardness, roughness, color, and morphology of enamel after Er, Cr:YSGG laser irradiation, followed by application of three types of bioactive glasses-based resin infiltrants, and the samples groups were challenged with the pH cycle. Methodology: Experimental photoactivated resin infiltrants were synthesized using dimethacrylate resins, whereby three different types of bioactive glasses (BGs), i.e., 45S5, fluoridated-BG (F-BG), and borosilicate-BG (B-BG), were incorporated into the resin system. Initially, white spot lesions were created artificially on the toosth enamel surface, then irradiated with Er, Cr:YSGG laser. Then, the resin-only and BG-based resins were infiltrated on the enamel surface. All samples were pH challenged for 14 days, and the micro-hardness, surface roughness, surface morphology, and color stability (ΔE) analyses were conducted before and after the 14 days pH challenge. Results: After laser irradiation, the micro-hardness was significantly high with 45S5 group compared to resin-only (p = 0.021), F-BG (p = 0.042), and B-BG (p = 0.001) groups. After the pH challenge, the micro-hardness values for all groups were reduced significantly (p ≤ 0.05). The surface roughness was least with the resin-only group and showed a non-significant difference with F-BG (p = 0.34) and significant differences with both B-BG (p = 0.005), and 45S5 (p = 0.010) groups. After the pH cycle, the roughness of all groups was increased significantly (p ≤ 0.05), except B-BG group showed a non-significant difference (p = 0.528). The B-BG group showed significantly high ΔE between day 0 and baseline compared to resin-only (p = 0.0008), F-BG (p = 0.017), and 45S5 (p = 0.029), whereas between day 14 and baseline, the lowest ΔE value was observed for B-BG (14.2 ± 2.10) and maximum for the resin-only (20.57 ± 2.47) group. The SEM images showed pitting on the surface of all resin infiltrant groups after 14 days of pH challenge. Conclusion: The morphological difference was observed after the laser irradiation on the enamel surface. The differences in micro-hardness, surface roughness, and color were observed after the application of experimental resin infiltrants and significant differences were observed after the pH challenge.